Effects of Virtual Reality Simulation on Worker Emergency Evacuation of Neonates. (8th October 2018) - Farra, Sharon; Hodgson, Eric; Miller, Elaine T.; Timm, Nathan; Brady, Whittney; Gneuhs, Matt; Ying, Jun; Hausfeld, Jackie; Cosgrove, Emily; Simon, Ashley; Bottomley, Michael
ABSTRACT: Objective: This study examined differences in learning outcomes among newborn intensive care unit (NICU) workers who underwent virtual reality simulation (VRS) emergency evacuation training versus those who received web-based clinical updates (CU). Learning outcomes included a) knowledge gained, b) confidence with evacuation, and c) performance in a live evacuation exercise. Methods: A longitudinal, mixed-method, quasi-experimental design was implemented utilizing a sample of NICU workers randomly assigned to VRS training or CUs. Four VRS scenarios were created that augmented neonate evacuation training materials. Learning was measured using cognitive assessments, self-efficacy questionnaire (baseline, 0, 4, 8, 12 months), and performance in a live drill (baseline, 12 months). Data were collected following training and analyzed using mixed model analysis. Focus groups captured VRS participant experiences. Results: The VRS and CU groups did not statistically differ based upon the scores on the Cognitive Assessment or perceived self-efficacy. The virtual reality group performance in the live exercise was statistically ( P <.0001) and clinically (effect size of 1.71) better than that of the CU group. Conclusions: Training using VRS is effective in promoting positive performance outcomes and should be included as a method for disaster training. VRS can allow an organization to train, test, and identify gaps in current emergency operation plans. In the unique case of disasters, which are low-volume and high-risk events, the participant can have access to an environment without endangering themselves or clients. ( Disaster Med Public Health Preparedness. 2019;13:301–308)